Pengelolaan Penilaian Pembelajaran Bahasa Inggris Kurikulum 2013 Di SMP Negeri 4 Klaten - Handayani, Sri, Dr. Sumardi, M. Si, Dr. Anam Sutopo, M. Hum (2017)
This study aims at: (1) describing the assessment of attitude aspect in English language learning Curriculum 2013 at SMP Negeri 4 Klaten, (2) describing the assessment of knowledge aspect in English language learning Curriculum 2013 at SMP Negeri 4 Klaten, and (3) describing the assessment of skill aspect in English language learning curriculum 2013 at SMP Negeri 4 Klaten. The method of the research is qualitative research design using an ethnographic approach. The data used are primary and secondary data. The data analysis tecknique uses interactive model. While data collecting method uses: interview, observation, and documentation. The results of the study are: (1) the assessment management of attitude aspect in the teaching of English Curriculum 2013 at SMP Negeri 4 Klaten, the material for the competencies of spiritual and social attitudes delivered and achieved through indirect teaching, the aspects of attitude assessment include observation, self-assessment, peer assessment, and journal, (2) the asssessment management of knowledge aspect in the teaching of English Curriculum 2013 at SMP Negeri 4 Klaten has been implemented in accordance with syllabus of English learning Curriculum 2013 applying the principles of mastery learning, authentic, and continuous. The assessment of knowledge aspect carried out using the tecknique of written test through daily test after a basic competence has completely taught, middle term test, and final term test. The materials for knowledge and skill competencies are minimally as they are in syllabus and can be developed by teacher,. and (3) the assessment management of skill aspect in the teaching of English curriculum 2013 at SMP Negeri 4 Klaten uses the teckniques of performance, product, and portofolio. These teckniques are regarded as the most suitable with the characteristics of English learning material.